2011
DOI: 10.5713/ajas.2011.10334
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Sodium Gluconate, Mannan Oligosaccharide and Potassium Diformate on Growth Performances and Small Intestinal Morphology of Nursery Pigs

Abstract: This study was conducted to compare the effects of dietary supplementation of Sodium Gluconate (SG), Mannan Oligosaccharide (MOS) and Potassium Diformate (PDF) on growth performance and small intestinal morphology in nursery piglets. One hundred forty four female piglets (11.69±0.71 kg) were divided into 4 treatments with six replicates of six pigs each. The pigs received a control diet or diets supplemented with SG, MOS and PDF at 2,500, 3,000 and 8,000 ppm; respectively, for 6 weeks. Supplementation of SG, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 22 publications
5
23
1
Order By: Relevance
“…In addition, the trend of higher N retention is in accordance with the better growth rate observed at this stage. These results agree with those observed by Poeikhampha and Bunchasak (2011), which showed that dietary supplementation with mannanoligosaccharide and organic acid salts (gluconate and diformate) reduced ammonia production in the large intestine, indicating that less N was available for fermentation. Devi et al (2016) also observed improvement in DM, GE, and N digestibility with diets supplemented only with benzoic acid and not with an additive mix, similarly to the present trial.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition, the trend of higher N retention is in accordance with the better growth rate observed at this stage. These results agree with those observed by Poeikhampha and Bunchasak (2011), which showed that dietary supplementation with mannanoligosaccharide and organic acid salts (gluconate and diformate) reduced ammonia production in the large intestine, indicating that less N was available for fermentation. Devi et al (2016) also observed improvement in DM, GE, and N digestibility with diets supplemented only with benzoic acid and not with an additive mix, similarly to the present trial.…”
Section: Discussionsupporting
confidence: 83%
“…Poeikhampha andBunchasak (2011), Corassa et al (2012), and Giannenas et al (2016), working with different acid and mannanoligosaccharides mixtures, were able to observe the synergistic effect of these additives, mainly on ADG and G:F. The results of the present study did not show synergy of these additives on G:F. However, there was improvement on ADG in the starter phase. This result was not repeated when analysing the whole evaluation period, showing that this gain was diluted in the total period.…”
Section: Discussionmentioning
confidence: 29%
“…As a natural nutritional supplement MOS may offer a novel approach to balance the intestinal microbiota to beneficial direction and thus may improve overall gut health and welfare (Castillo et al 2008). Also, dietary MOS may maintain the intestinal morphology and absorptive function by increasing the villous height : crypt depth ratio of the gut in weaned pigs (Poeikhampha and Bunchaska 2011). The effect of MOS on pig performance was analysed in several meta-analyses which reported growth rate improvements in nursery rather than in fattening pigs (Miguel et al 2004;Z h a o et al 2012).…”
Section: Immunity Gut Microbiota Growth Swinementioning
confidence: 99%
“…Results showed that dietary mannan products increase the villous height: crypt depth ratio in young broilers [ 33 ] and turkey [ 14 ] and also in weaned piglets [ 34 , 35 ]. In a recent study with nursery pigs, Poeikhampha and Bunchasak [ 36 ] found that 3 g MOS/kg in the diet resulted in increased crypt depth in the jejunum. An increased villous height: crypt depth ratio is generally associated with a bigger absorptive surface; this ratio is, however, usually reduced during the initial post-weaning period [ 37 ].…”
Section: Mode Of Action Of Dietary Mosmentioning
confidence: 99%